The wax child - Ravn, Olga (New Directions Publishing Corporation, 2025)
"In seventeenth-century Denmark, Christenze Kruckow, an unmarried noble- woman, is accused of witchcraft. She and several other women are rumored to be possessed by the Devil, who has come to them in the form of a tall headless man and gives them dark powers: they can steal people's happiness, they have performed unchristian acts, and they can cause pestilence or even death. They are all in danger of the stake. The Wax Child, narrated by a wax doll created by Christenze Kruckow, is an unsettling horror story about brutality and power, nature and witchcraft, set in the fragile communities of premodern Europe. Deeply researched and steeped in visceral, atmospheric detail, The Wax Child is based on a series of real witchcraft trials that took place in Northern Jutland in the seventeenth century. Full of lush storytelling and alarmingly rich imagination, Olga Ravn weaves in quotes from original sources such as letters, magical spells and manuals, court documents, and Scandinavian grimoires"-- Provided by publisher.